Kajian Rancang Bangun Alat Sistem Keamanan Pada Brankas Perhiasan Dengan Menggunakan Face Recognition Dan Fingerprint Berbasis Arduino Mega2560 Terkendali Smartphone Android - Qadir Aziz; Khalid Arifin (Politeknik Kampar, 2023)
The security system is an effort to prevent theft or loss of an object. One of them is the security system on the jewelery safe door which is vulnerable and the possibility of occurrence is quite large. In a safe today it is very necessary to have a security system, in order to anticipate the danger of theft that can occur unexpectedly. Not everyone can open this safe door, because this safe door has a tool that can open only the owner's safe door by using face recognition and fingerprints. (Okta, et al, 2021)